A demographic survey on the prevalence of gastrointestinal parasites based on socioeconomic determinants in Pakistan - Irum, Shumaila; Ahsan, Arbab; Ahmed, Haroon; Khan, Aisha; Yayi, Guan; Mehboob, Mudabbar; Simsek, Sami (J Infection Developing Countries, 2021)
Introduction: The present study was conducted to investigate prevalence of intestinal parasites and the risk factors related to socio-demographic characteristics of patients admitted in pathology ward, General Hospital, Gujranwala. Methodology: 318 stool samples were collected from patients and examined under light microscope by using wet mount technique. While socio-demographic information was collected in the form of a questionnaire. Results: The results showed seven (n = 7) species of intestinal parasites were prevalent in stool samples of patients. Among them, four (n = 4) were helminth and three (n = 3) were protozoan parasites causing single and mixed infections. Overall prevalence of intestinal parasites was 78.3% (n = 249/318) considering both male and female patients. Highest prevalence was recorded for A. lumbricoides (n = 125, 39.3%) followed by H. nana (n = 10, 3.1%), S. stercoralis and T. saginata (n = 6, 1.9%). Among protozoan parasites, higher prevalence was recorded in G. lamblia (n = 23, 7.2%) followed by E. histolytica (n = 21, 6.6%). Among single infections, the most prevalent parasite was A. lumbricoides and less prevalent parasites were S. stercoralis and T. saginata. The factors that had significant effect (p < 0.05) on prevalence of parasitic species were contaminated water, food, soil, and surrounding environment. Conclusions: The present study determined that the parasite helminth (A. lumbricoides, H. nana, S. stercoralis, T. saginata) and protozoan (G. lamblia and E. histolytica) are common that pose an important public health concern in Pakistan.
Keywords: Gastrointestinal parasites; protozoa; helminth; human; Pakistan